Conceptualization and application of a healthcare systems thinking model for an educational system. Issue 9 (2nd September 2022) - Selvik, Jon T.; Abrahamsen, Eirik B.; Moen, Vegard
ABSTRACT: Systems thinking is challenging but clearly important in higher education to understand relationships between different elements influencing the quality and student learning and achievement. A similar challenge is found in healthcare, where patient safety activities are more and more seen and dealt with in a broader system perspective. A recognized and useful conceptual model employed in this area and relevant to complex sociotechnical systems, to identify interactions and outcomes of patient safety-related activities, is the Systems Engineering Initiative for Patient Safety (SEIPS). This is a model that can be used in healthcare for the identification of unintended effects when considering improvement initiatives. In this article, we question and discuss the rationale and applicability of the principles of this model in an educational context, for student focus instead of patient safety, to identify and understand interactions influencing learning. For example, we discuss the effect of student learning from exams, where the model can be used to identify and discuss different pros and cos related to the overall objective of achieving educational improvements. Based on the discussion, we claim that the principles of the SEIPS model serve well as a conceptual framework for analysing the benefits of educational efforts from a systems thinking perspective. A modified model, named STEQ, being well suited for the educational context, is presented in the article.